2020
DOI: 10.1038/s42003-020-0796-5
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas12a technology combined with immunochromatographic strips for portable detection of African swine fever virus

Abstract: African swine fever virus (ASFV), the aetiological agent of African swine fever (ASF), causes lethal haemorrhagic fever in domestic pigs with high mortality and morbidity and has devastating consequences on the global swine industry. On-site rapid and sensitive detection of ASFV is key to the timely implementation of control. In this study, we developed a rapid, sensitive and instrument-free ASFV detection method based on CRISPR/Cas12a technology and lateral flow detection (named CRISPR/Cas12a-LFD). The limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 22 publications
0
95
0
2
Order By: Relevance
“…Expression and Purification of Recombinant Cas12a Proteins: LbCas12a was expressed and purified as previously described. [11] In brief, the coding sequences of LbCas12a were codon-optimized and synthesized by Genscript (Nanjing, China) and then cloned into pET28a (Novagen) with a C-terminal 10× His tag. The coding sequence of AsCas12 was synthesized by Genscript (Nanjing, China) as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression and Purification of Recombinant Cas12a Proteins: LbCas12a was expressed and purified as previously described. [11] In brief, the coding sequences of LbCas12a were codon-optimized and synthesized by Genscript (Nanjing, China) and then cloned into pET28a (Novagen) with a C-terminal 10× His tag. The coding sequence of AsCas12 was synthesized by Genscript (Nanjing, China) as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Cas12a-Mediated Nucleic Acid Detection: The detection assays were performed as previously reported with minor modifications. [11] In a 20 µL detection assay, with 200 ng LbCas12a protein, 25 × 10 −12 m ssDNA FQ probe sensor, 1 × 10 −6 m crRNA, and 2 µL of the sample in a reaction buffer (100 × 10 −3 m NaCl, 50 × 10 −3 m Tris-HCl, 100 µg mL −1 BSA(bovine serum albumin), pH 7.9) supplied with 10 × 10 −3 m MgCl 2 or MnSO 4 , were incubated at 37°C until detection. A PerkinElmer EnSpire reader with the excitation at 485 nm and emission at 520 nm was used for fluorescence detection.…”
Section: Methodsmentioning
confidence: 99%
“…So the clinical application of this method is limited. Previous studies also showed that CRISPR system can detect ASFV [ 26 , 27 ]. However, they did not compare the sensitivity of CRISPR with qPCR, the most sensitive method in the detection of ASFV until now, indicating that further research is needed in the sensitivity analysis of the CRISPR in ASFV detection.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the simplicity of the CRISPR/Cas-based detection system allows the rapid development of diagnostic methods for an emergency outbreak of infectious diseases. For example, integrating later flow assay (CORDS, CRISPR/Cas12a-LFD) and naked-eye detection (CRISPR/Cas-based colorimetric platform, fluorescence-based POC system), four groups quickly developed Cas12a-based on-site diagnostic assays for African swine virus (ASFV), an emergence virus for the global swine industry (Table 2) [44][45][46][47]. For the current COVID-19 pandemic [48], several research groups are developing CRISPR/Cas-based diagnostic assay [49][50][51][52][53].…”
Section: The Strengths Of Crispr/cas Based Pathogen Detection Systemsmentioning
confidence: 99%
“…Isothermal amplification that does not require instruments has been widely integrated into CRISPR-based detection [ 7 ]. For signal readout, more equipment-free methods, such as later flow assay or naked-eye view under light, should be introduced [ 41 , 45 , 46 , 55 ]. Currently, the store and delivery of the CRISPR-based detection system still need a cold chain.…”
Section: Future Perspectivesmentioning
confidence: 99%